A systematical weight function modified critical distance method to estimate the creep-fatigue life of geometrically different structures. (September 2019) - Li, Zhenlei; Shi, Duoqi; Li, Shaolin; Yang, Xiaoguang; Miao, Guolei
Graphical abstract: Highlights: A novel method was proposed to determine the damage zone of structures. A geometrical feature factor was defined to represent the stress concentration. LCF and creep weight functions were proposed to assess the effect of stress gradient. A systematic method was developed to estimate the creep-fatigue life of structures. Abstract: This paper develops a novel weight function modified critical distance method to estimate the creep-fatigue lives of geometrically complex structures. A geometrical feature factor was defined to account for the geometry-induced stress gradient, namely the average normalized stress gradient. The conventional weight function was modified using this concept to assess the weight effect of stress distribution on the low-cycle fatigue (LCF) and creep lives, respectively. The weight function modified critical distance methods were verified by the LCF and the creep test data of the specimens with significantly different geometries. Furthermore, creep-fatigue experiments on the full-scale hollow and solid turbine blades were conducted. The creep-fatigue lives of turbine blades were predicted using the systematical weight function modified methodology. The predicted results showed a good agreement with the experimental lives. Compared with other models, this novel method achieves a significantly better accuracy in the case of LCF, creep and creep-fatigue life predictions.